PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI PT NINDOMARCO PRISMATAMA CABANG BOGOR 2 - Ilyas, Yasnimar; Novianti, Nia (Economicus, 2019)
The results showed 1) There was a positive and significant influence of motivation on the performance of employees of PT Unggul Karya Semesta Bogor with a tilapia regression coefficient of 0.409 and t count = 11.204 > t table 1.979 which proved the first hypothesis was accepted. 2) There is a positive and significant influence of transformational leadership on the performance of employees of PT Unggul Karya Semesta Bogor with a regression coefficient of 0.170 and t count = 4.443> t table 1.979 which proves the second hypothesis is accepted. 3) There is a positive and significant influence of organizational culture on the performance of employees of PT Unggul Karya Semesta Bogor with a regression coefficient value of 0.403 and t count = 9461> t table 1.979 which proves the second hypothesis is accepted. 4) Simultaneous hypothesis test results known that the calculated F value of 168,176> F table 2,445 has proves that together with motivation, transformational leadership and organizational culture have a significant effect on employee performance. 5) The coefficient of determination test results obtained adjusted R² value of 0.799.